CRITERIA, INDICATORS AND LEVELS OF FORMATION READINESS OF FUTURE SOCIAL WORKERS TO USING INTERACTIVE TECHNOLOGIES IN PROFESSIONAL ACTIVITY - Хоменко-Семенова, Л. О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2014)
The article is devoted to actual problem of training future social workers, whose professional level must comply with today’s requirements. The paper discloses the essence of the content of the readiness of future social workers to using interactive technologies in professional work, substantiated criteria, indicators and levels of formation determined readiness